2022
DOI: 10.3390/molecules27206804
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease as a Major Public Health Concern: Role of Dietary Saponins in Mitigating Neurodegenerative Disorders and Their Underlying Mechanisms

Abstract: Saponins are triterpenoid or steroidal glycosides and are an important group of naturally occurring compounds of plant origin. They exhibit diverse pharmacological potentials including radical scavenging, as well as neuroprotective, anti-diabetic and anti-inflammatory activities, owing to their diverse chemical scaffolds. Saponins consist of an aglycone part (non-sugar) and a glycone part (sugar) and have at least one glycosidic (C–O sugar bond) linkage present between the glycone and aglycone mostly at C-3. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 125 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…ACh also modulates the release of other neurotransmitters such as dopamine, norepinephrine and serotonin. The number of receptors and transporters, as well as the secreted volume of norepinephrine and serotonin, are reduced in AD, resulting in reduced cognitive performance, memory loss, increased anxiety, agitation, aggression and other behavioral disturbances in dementia patients [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Pathophysiological Mechanisms In Alzheimer’s Diseasementioning
confidence: 99%
“…ACh also modulates the release of other neurotransmitters such as dopamine, norepinephrine and serotonin. The number of receptors and transporters, as well as the secreted volume of norepinephrine and serotonin, are reduced in AD, resulting in reduced cognitive performance, memory loss, increased anxiety, agitation, aggression and other behavioral disturbances in dementia patients [ 61 , 62 , 63 , 64 , 65 ].…”
Section: Pathophysiological Mechanisms In Alzheimer’s Diseasementioning
confidence: 99%
“…Ischemic stroke, which causes a burst of infarctions in the center of a hypoperfusion zone, is an acute neurotoxic process. Neurodegenerative diseases like Parkinson’s and Alzheimer’s are examples of chronic neurotoxicity (AD) ( Gaur et al, 2014 ; Abduljawad et al, 2022 ; Hassan et al, 2022a ). Recent studies showed that plant based active ingredients are effective in neurodegenerative disease ( Wei et al, 2021 ; Hassan et al, 2022b ; Mahnashi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its effects on body composition, there is growing evidence that a ketogenic diet may be a potential therapeutic approach for Alzheimer’s disease or other types of cognitive impairment via inhibition of pro-inflammatory cytokines, such as interleukin-1β (IL-1β) and tumor necrosis factor α (TNF-α) [ 19 , 20 , 21 ]. These cytokines are also known to accelerate catabolism, induce contractile dysfunction, disrupt myogenesis, and overall modulate muscle tissue loss (summarized in [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%